Empowering Elementary School Teachers through AI and Deep Learning Training Based on Participatory Action Research: Pemberdayaan Guru Sekolah Dasar melalui Pelatihan AI dan Deep Learning Berbasis Participatory Action Research - Sunoko Setyawan; Aan Erlyana Fardhani; Zakiyah Tasnim; Bea Hana Siswati (DARMADIKSANI, 2025)
This community service program aims to enhance elementary school teachers' technology literacy through training in artificial intelligence (AI) and deep learning technologies, conducted within the Teacher Working Group (KKG) Cluster 02, Rambipuji District, Jember Regency. The activities were carried out using a Participatory Action Research (PAR) approach, consisting of planning, action implementation, reflection, and evaluation stages. Evaluation results showed a significant improvement in participants' knowledge scores, with the average increasing from 51.1 (pre-test) to 81.8 (post-test). Participant engagement was also high, with over 85% of teachers attending all sessions and actively participating in discussions and hands-on practices. Classroom implementation reflections indicated that 80% of the teachers successfully attempted to create digital-based teaching media, although most still required further assistance. These outcomes demonstrate that the PAR approach, supported by practical modules and contextual mentoring, is effective in improving elementary school teachers’ technology literacy, while also promoting creative and adaptive learning in the digital era. This program can be recommended as a teacher empowerment model that is replicable in other regions with appropriate local contextual adjustments.